Repeat Interruptions Modify Age at Onset in Myotonic Dystrophy Type 1 by Stabilizing DMPK Expansions in Somatic Cells - Pešović, Jovan; Perić, Stojan; Brkušanin, Miloš; Brajušković, Goran; Rakočević-Stojanović, Vidosava; Savić-Pavićević, Dušanka (Frontiers in Genetics, 2018)
CTG expansions in DMPK gene, causing myotonic dystrophy type 1 (DM1), are characterized by pronounced somatic instability. A large proportion of variability of somatic instability is explained by expansion size and patient’s age at sampling, while individual-specific differences are attributed to additional factors. The age at onset is extremely variable in DM1, and inversely correlates with the expansion size and individual-specific differences in somatic instability. 3-5% of DM1 patients carry repeat interruptions and some appear with later age at onset than expected for corresponding expansion size. Herein, we characterized somatic instability of interrupted DMPK expansions and the effect on age at onset in our previously described patients. Repeat-primed PCR showed stable structures of different types and patterns of repeat interruptions in blood cells over time and buccal cells. Single-molecule small-pool PCR quantification of somatic instability and mathematical modeling showed that interrupted expansions were characterized by lower level of somatic instability accompanied by slower progression over time. Mathematical modeling demonstrated that individual-specific differences in somatic instability had greater influence on age at onset in patients with interrupted expansions. Therefore, repeat interruptions have clinical importance for disease course in DM1 patients due to stabilizing effect on DMPK expansions in somatic cells.